The Apology of Quadratus - Foster, Paul 1966- (2006)
Quadratus is perhaps the least familiar text among the artificial corpus known as the Apostolic Fathers. In fact this fragment is excluded in many editions of these texts. This discussion attempts to date and locate the fragment, to analyze its single argument, and to understand this writing in relation to the apologetic tradition that emerged in second-century Christianity.
Keywords: Apologizing; Apology; Apostolic Fathers; Christian biography; Christianity; Hadrian; Healings; Oral Tradition; Quadratus